GAMBARAN TINGKAT PENGETAHUAN MASYARAKAT TENTANG SWAMEDIKASI OBAT INFUENZA DI DUSUN SOKA KLATEN BULAN FEBRUARI 2023 - Yulianto, Danang (Jurusan Farmasi, Politeknik Kesehatan Kementerian Kesehatan Aceh, 2024)
Based on data from the Central Statistics Agency in 2021, the prevalence of people in Indonesia who do self-medication is 84.23%.. Some studies show that influenza is a disease that many people complain about during self-medication. Self-medication against influenza is not a completely safe treatment, so knowledge of the use of infuenza drugs must be required. The purpose of this study was to determine the level of public knowledge about influenza medicine self-medication in Soka, TambongWetan, Kalikotes, Klaten Regency.The study was conducted in a quantitative descriptive observational manner involving 97 research respondents taken by purposive sampling method. Data was taken using questionnaire that had previously been tested for validity and reliability, data analysis with univariate analysis using Microsoft excelto get an overview of the frequency and percentage of knowledge levels so that they were categorized into high, medium and low.The results showed that 63.92% of respondents had a good level of knowledge about influenza drug self-medication, 35.05% had a sufficient level of knowledge, 1.03% had a lack of knowledge. Based on the results of the study, it can be concluded that the majority of respondents have a good level of knowledge about influenza drug self-medication.